2018
DOI: 10.3389/fmicb.2018.01364
|View full text |Cite
|
Sign up to set email alerts
|

Swine-Derived Probiotic Lactobacillus plantarum Inhibits Growth and Adhesion of Enterotoxigenic Escherichia coli and Mediates Host Defense

Abstract: Weaning stress renders piglets susceptible to pathogen infection, which leads to post-weaning diarrhea, a severe condition characterized by heavy diarrhea and mortality in piglets. Enterotoxigenic Escherichia coli (ETEC) is one of typical strains associated with post-weaning diarrhea. Thus, prevention and inhibition of ETEC infection are of great concern. Probiotics possess anti-pathogenic activity and can counteract ETEC infection; however, their underlying mechanisms and modes of action have not yet been cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 55 publications
9
72
1
Order By: Relevance
“…and pBD3) were upregulated after exposure to L. plantarum ZLP001 in IPEC-J2 cells (Wang, Zeng, et al, 2018), suggesting that L. plan- (Liu et al, 2010;Yi et al, 2018). We observed that the L. plantarum 299v treatment significantly increased the mRNA levels of ileal TLR2, TLR4, TLR6 and TLR9 but did not change the levels of jejunal TLRs.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…and pBD3) were upregulated after exposure to L. plantarum ZLP001 in IPEC-J2 cells (Wang, Zeng, et al, 2018), suggesting that L. plan- (Liu et al, 2010;Yi et al, 2018). We observed that the L. plantarum 299v treatment significantly increased the mRNA levels of ileal TLR2, TLR4, TLR6 and TLR9 but did not change the levels of jejunal TLRs.…”
Section: Discussionmentioning
confidence: 59%
“…A previous study indicated that supplementation with L. plantarum CGMCC 1,258 resulted in higher levels of occludin mRNA in the jejunum of young piglets (Yang, Jiang, Zheng, Wang, & Yang, ). In vivo, L. plantarum ZLP001 treatment alleviated the reduced expression of claudin‐1 , occludin and ZO‐1 caused by ETEC (Wang, Zeng, et al, ). These data indicated that L. plantarum could improve the expression of TJs proteins in the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, L. rhammosus GG exhibited excellent mucus adhering characteristics partly due to its specific pili SpaCBA (Hampe & Roth, ). Therefore, probiotics may preoccupy and compete for pathogen‐binding sites, leading to interference with pathogenic adhesion and resistance colonization (Wang et al, ). Some oral pathogenic strains like Streptococcus mutans and S. sobrinus forming biofilm give rise to the development of dental caries.…”
Section: Antimicrobial Activity Of Probioticsmentioning
confidence: 99%